Pengembangan Sistem Informasi Geografis Pemetaan Tower Base Transceiver Station (BTS) Berbasis WEB - Budi Hartanto; Hilda Dwi Yunita; Devi Cantika (Jurnal Teknologi dan Informatika (JEDA), 2021)
AbstractGeographic Information System (GIS) is an effective medium to identify the location of cellular operator telecommunication towers in finding locations that are not covered by cellular operator telecommunication tower signals and supports the placement of new cellular operator telecommunication towers. Based on this, the problems that arise are difficulties in obtaining information on the location of telecommunication towers for cellular operators, differences in distances that can be traveled, the difficulty of the BTS (Base Transceiver Station) Development and Control Supervisory Board knowing how many telecommunication towers from each provider in Bandar Lampung. and the absence of a system to identify the location of cellular operator telecommunication towers in Bandar Lampung digitally. Based on this, the researcher proposes a Geographic information system for mapping tower bases transceiver stations (BTS). From the results of the research that has been done, the Geographic Information System (GIS) can identify the tower location points. With this system, it is hoped that this system can be used as a reference for the BTS Development and Control Supervisory Agency in identifying the location of cellular operator telecommunication towers in Bandar Lampung as well as being a reference for the BTS (Base Transceiver Station) Development and Control Supervisor in the construction and placement of new cellular operator telecommunication towers in Bandar Lampung. Bandar Lampung.